Aplikasi Augmented Reality Perlengkapan Militer Menggunakan Algoritma FAST Corner Dan Lucas Kanade - Nanda Maulana Hidayat (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Knowledge of military equipment is not only obtained through exhibitions, with the development of information technology can be obtained through applications. The use of augmented reality applications can be used as an example in the knowledge of military equipment in three dimensions. This design aims to provide knowledge to the general public by using Augmented Reality technology. This design uses the ADDIE method and the FAST Corner and Lucas Kanade algorithms. The design resulted in an application containing the introduction of military equipment consisting of berets, Boonie hats, patrol hats, helmets, glasses, large bags, first aid kits (First Aid In accidents), knives, remote weapons, and medium weapons. Brief information about each military equipment is attractively designed to make the general public easy to understand in using applications that can be run on the Android platform.